Future of Work: Mentoring, Tinkering and Skilling (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
Potential alterations and systematic changes are the need of the hour in this ever changing G20 world. This explains the universal concept that change is the unchangeable law of nature. Human society, its eco-system as well as patterns and practices change with the march of time. Technological advancement and scientific progress have resulted in a significant paradigm shift in the world of work. This shows the changing trends of future of work that have paved the way for human resource building through use of science,technology, innovative pedagogy and their integration through mentoring, tinkering skilling and upskilling. In other words, development of human potential by applying innovation, creativity, experiments, critical thinking, problem-solving and technological interventions like robotics, drone technology, artificial intelligence, virtual reality, augmented reality and the like.A rising trend in the world of work is vocational education and vocationalization of education. Accordingly, changes are required in curriculum, pedagogy, textbooks, teacher training, resource support and even bringing digital resources and innovativeteaching-learning materials. This paper is a collection of and reflection upon different perspectives of future of work and skill development through particularly by mentoring, tinkering, skilling and upskilling. As such it reflects upon the rising trends of the world of work with new opportunities, new technologies, new market-places, productive jobs and even techno-savvy human resources. Rapid advancement in coding, automation, digital technology and use of robotics together with innovative and integrated pedagogicalpractices are the future trends of work and occupation which constitute the core concern of this paper. What is certain is that future is uncertain. Therefore, efforts are to be made for mentoring, tinkering and skilling the work force by using technological interventions.